Group work : a practical guide to developing groups in agency settings - Alle-Corliss, Lupe , 1956-; Alle-Corliss, Randy , 1953- (Wiley & Sons, 2009)
Because of its cost-effective nature, group work has become the treatment approach of choice in a broad range of human service agencies. This practical guide offers the skills and awareness needed to effectively navigate the many intricacies of working in groups within diverse agency settings.